Coumarin-Mediated Growth Regulations, Antioxidant Enzyme Activities, and Photosynthetic Efficiency of Sorghum bicolor Under Saline Conditions - Sultana, Robina; Wang, Xiukang; Azeem, Muhammad; Hussain, Tabassum; Mahmood, Athar; Fiaz, Sajid; Qasim, Muhammad (Frontiers in Plant Science, 2022)
Secondary metabolites, such as phenolic compounds, play an important role in alleviating salinity-induced negative effects in plants. The present study focused on seed priming and foliar application of a potent phenolic compound, coumarin, to induce salinity tolerance in Sorghum bicolor var. SS-77. Based on pilot experiment, 100 mg L−1 concentration of coumarin was applied to mitigate the negative effects of salinity on Sorghum, grown at 0, 100, and 200 mM NaCl under netted greenhouse conditions. Coumarin was applied to each salinity treatment in four different ways (i) non-primed control (NP), (ii) seed priming (COP), (iii) foliar application (COF), and (iv) a combination of seed priming and foliar application (COPF). Salinity stress significantly reduced the plant growth, biochemical attributes, and photosynthetic efficiency of Sorghum, whereas coumarin treatments (COP, COF, and COPF) showed a significant increase (P< 0.01) in above-mentioned parameters at all salinities. Among all, the combined treatment (COPF) showed maximum increase in growth, biochemicals, photosynthetic pigments, antioxidant enzymes, and photosynthetic efficiency parameters. Therefore, it is suggested that a combination of seed priming and foliar spray of 10 mg L−1 coumarin is more suitable than their individual applications. It is an environment friendly and economically feasible approach that will be used to improve salinity tolerance of Sorghum and helpful to get considerable biomass from saline degraded lands to fulfill food, fodder, and energy demands of the ever-growing population.